The Impact of Citizenship Pressure on Organizational Citizenship Performance: A Three-Way Interactive Model - Liu, Yazhen; Fu, Jingtao; Pervaiz, Sabeeh; He, Qi (Frontiers in Psychology, 2021)
Citizenship pressure has recently been a hot topic in organizational citizenship behavior research since it aids in understanding the driving mechanism of organizational citizenship behavior. Previous research, however, has revealed discrepancies in the connection. This paper develops a theoretical model of the impact of citizenship pressure on organizational citizenship performance based on expectation theory. A leader-employee paired questionnaire was used to evaluate the hypotheses. The results indicate that organizational citizenship performance is positively influenced by citizenship pressure. The connection between organizational citizenship performance and citizenship pressure is positively moderated by transformational leadership. The better the transformational leadership, the greater the influence of citizenship pressure on organizational citizenship performance. Furthermore, the impact of transformational leadership on the link between citizenship pressure and organizational citizenship performance is dependent on employees' political skill. When individuals with strong political skill encounter transformational leadership, the relationship between citizenship pressure and organizational citizenship performance is minimal. On the contrary, this relationship is enhanced when personnel with limited political skill are confronted with transformational leadership.